Agility in organizations: A bibliographic investigation into the state of the art - Tommi Tapanainen; Ahmad Farhan; Hannu Salmela; Xue Li (신산업경영저널, 2024)
Research on agility, which started to become popular in the 1990’s, has over the years coalesced into multiple distinct streams with often little cross-fertilization. This has made it difficult to consolidate what has been learned about agility across the separate streams of research. Although qualitative literature reviews have been produced, due to the large number of articles these reviews can only capture a limited slice of the literature. In contrast, this article carries out a systematic literature review on agility in organizations using a bibliographic coupling and content analysis. We find three main clusters of research around agility: (1) software development agility, (2) supply chain management agility, and (3) strategic IT agility. Our findings show that information technology is a major contributor to agility research, and suggest shared perspectives on agility that combine ideas from these clusters as avenues for future research. Such shared perspectives can advance agility research, and more importantly, may offer pathways for theorizing in specific, emerging areas of management. KCI Citation Count: 0